Smart Home - lubna; Roaa (My University, 2023)
This project is based on building a model that simulates home automation with different operating modes that can also be controlled by a mobile application, a model of a miniature house has been developed so that it has many advantages and characteristics, making it easier for the customer to control the house in terms of lighting, doors and windows through a mobile phone easily, as for the external doors, some of them will be controlled Through mobile application, some via the card, and an automatic air conditioning system will be added so that the house temperature is adjusted automatically, and we will rely on sensors in particular in our project such as flame sensors to identify the presence of a fire in the house, and water sensors to check rain and control the Opening and closing windows, in addition, an automatic irrigation system that works based on the moisture of agricultural soil, using a moisture sensor as a measure of humidity, also Remotexy application used to control the features, so our project combines the IOT and automation technology, which makes life easier.